Clostridium difficile: padronização e avaliação de métodos de diagnóstico, ocorrência em seres humanos e animais e desenvolvimento de um modelo experimental em hamsters - Rodrigo Otavio Silveira Silva (2014)
The aim of this study was to: (1) develop the detection of A/B toxins in cell culture assay; (2) evaluate three commercial enzyme immunoassays (EIAs) for diagnosis of CDI in humans, foals and piglets; (3) evaluate the frequency of CDI in humans, in piglets, in foals and in wild carnivores; (4) evaluate the ribotypes and antimicrobial susceptibility of C. difficile strains from various sources; (5) develop an model of CDI in Syrian hamsters. The standardized cell culture assay was able to detect A/B toxins from stool samples. All EIAs tested showed a high sensitivity and specificity for foals samples, and sensitivity under 60% for humans´ and piglets´ samples. The disease was confirmed for the first time in in wild felids and described for the first time in piglets and foals in Brazil. Thirteen different ribotypes were found and all C. difficile strains were susceptible to metronidazole, vancomycin, florfenicol, whereas resistance to oxytetracyclin, penicillin, tylosin and erythromicyn was detected. An animal model of ICD was developed in hamsters (Mesocricetus auratus) and now can be used for future pathogenesis, treatment and prevention CDI studies. As a conclusion, the present study confirms ICD as an important cause of diarrhea in animals and humans in Brazil. In addition, it highlighted the need of more studies about diagnosis and control methods of this disease.